2012
DOI: 10.1371/journal.pone.0050977
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Related Effects of Alcohol on Cognitive Functioning

Abstract: We assessed the suitability of six applied tests of cognitive functioning to provide a single marker for dose-related alcohol intoxication. Numerous studies have demonstrated that alcohol has a deleterious effect on specific areas of cognitive processing but few have compared the effects of alcohol across a wide range of different cognitive processes. Adult participants (N = 56, 32 males, 24 females aged 18–45 years) were randomized to control or alcohol treatments within a mixed design experiment involving mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 83 publications
7
106
0
1
Order By: Relevance
“…Experiment 1a and 1b showed that performance in the task is not impacted by mild-to-moderate physiological stress that impacted other tasks involving sustained attention. This result is somewhat consistent with the finding of Dry et al (2012), who showed TSP performance is only modestly (and not significantly) impacted by levels of alcohol consumption that impair a number of other cognitive tasks. This suggests that solutions to the TSP involve …”
Section: Reliability and Validitysupporting
confidence: 90%
“…Experiment 1a and 1b showed that performance in the task is not impacted by mild-to-moderate physiological stress that impacted other tasks involving sustained attention. This result is somewhat consistent with the finding of Dry et al (2012), who showed TSP performance is only modestly (and not significantly) impacted by levels of alcohol consumption that impair a number of other cognitive tasks. This suggests that solutions to the TSP involve …”
Section: Reliability and Validitysupporting
confidence: 90%
“…In this regard, effects of alcohol on risky behaviour are argued to be a result of pharmacologically-induced cognitive deficits (Dry, Burns, Nettelbeck, Farquharson, & White, 2012), leading to engagement in risky behaviours (Giancola, Josephs, Parrott, & Duke, 2010). To test this assertion, experimental researchers typically administer acute doses of alcohol to healthy, non-dependent participants and subsequently examine their risk-taking behaviour compared to those in non-alcohol consumption conditions.…”
Section: Whisky To Riskymentioning
confidence: 99%
“…In the main, theoretical perspectives posit that alcohol and risk-taking behaviour are driven by cognitive processes (Dry et al, 2012;Mocaiber et al, 2011). This body of work alludes to pharmacologically induced deficits in cognitive functioning leading to disinhibition (Leeman, Toll, Taylor, & Volpicelli, 2009) and increased attentional bias, or focal narrowing (Steele & Josephs, 1988;Steele & Josephs, 1990).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a variety of cognitive tasks, low-and moderatedose alcohol, relative to placebo, has produced deficient Field et al, 2010;Friedman et al, 2011), facilitated (Gilbertson et al, 2009;Sklar et al, 2012), and similar (Dry et al, 2012;Guillot et al, 2010;Milani & Curran, 2000) performance. Contradictory findings are also reported for identical tasks and similar alcohol concentrations (e.g., Dry et al, 2012, vs. Gilbertson et al, 2009.…”
mentioning
confidence: 99%